Three conceptions of nativism and the faculty of language. (May 2021) - Bouchard, Denis
Abstract: I compare three linguistic models based on different conceptions of nativism to determine whether they can provide revealing accounts of properties of natural languages, and whether the traits that these linguistic models require are evolutionarily plausible. The model based on Language-specific nativism in a broad sense contains rules, conditions, features and categories—Universal Grammar—to capture the empirical phenomena. Broad UG contains many domain-specific devices that are more descriptive than explanatory, and are unlikely to have evolved as irreducible properties of the brain. Language-specific nativism in a narrow sense tries to improve evolvability by restricting its core component to the operation set-Merge and a universal lexicon of innate concepts. But the transfer operations required to link the language-invariant expressions with actual expressions of natural languages turn out to be inapplicable. Evolvability is also problematic: the model ends up appealing to mystery on three key issues. Exapted Language Nativism posits that the human language capacity is not due to a brain development specifically devoted to language but is a side effect of a uniquely human capacity of detachment that enables an array of human-specific cognitive traits. Key among these traits is the capacity to form linguistic signs. Syntactic combinations emerge directly from the capacity to form combinatorial signs, a small natural subset of linguistic signs. The perceptual and conceptual elements of signs, and the extralinguistic cognition of speakers, have grounded prior properties that provide principled explanations of the data. The model has high evolvability since its core capacity of detachment is independently related to other phenotypic effects. Highlights: Minimalist Universal Grammar: Merge and a universal set of innate concepts. Transfer operations to link invariant expressions with actual sentences: inapplicable. The language capacity is a side effect of a uniquely human capacity of detachment. The key trait is the capacity to form linguistic signs. No move operation required: combinatorial signs, a natural subset of linguistic signs.